Acute Myocardial Infarction in a 25-Years-Old Male: Understanding the Risk and Comprehensive Management - Ardhani Galih; Cholid Tri Tjahjono; Sasmojo Widito; Evit Ruspiono (Universitas Brawijaya, 2023)
Acute coronary syndrome (ACS) in young adults is a rare entity, yet it occurs. We present a case of a man 25 years old with no history of certain diseases, suddenly come up with ST elevation myocardial infarct. Young patients have different risk factors, clinical features and prognosis as compared to elderly patients. The diagnosis of ACS is also often overlooked in this subset of population. Furthermore, it constitutes an important problem because of the devastating effect of this disease on the more active lifestyle of young adults. This case report was an attempt to look for the risk factors most prevalent in young patients and its management prior and during the hospital stay.